The Protection of Investor Rights in Margin Transactions By Securities Companies when Force Selling is Performed - Sulistyani, Ratu Vidi; Mashdurohatun, Anis; Hanim, Lathifah (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to analyze investor rights protection arrangements in the analysis of margin transaction financing and the implementation of investor rights protection arrangements in the analysis of margin transaction financing by Stock Exchange Companies when a share sale is forced. The research method applied is sociological juridical.The results of this study show The regulation on the protection of investor rights in the analysis of margin transaction financing by a Stock Exchange Company when a share sale is made by force has actually been regulated in a letter of agreement, which is stated in Bapepam-LK Rule Number VD6. The existence of these regulations has fulfilled the legal protection aspects for investors as regulated in the Civil Code, but has not fulfilled the investor legal protection aspects as regulated in the Capital Market Law and the Consumer Protection Law. The implementation of the protection of investors' rights in the analysis of margin transaction financing by the Stock Exchange Company when a forced sale of shares is carried out has been carried out through a contract accompanied by the implementation of an internal control system and the implementation of haircuts by the IDX.Keywords: protection, margin transactions, forced sell.